Durable Response of Spinal Chordoma to Combined Inhibition of IGF-1R and EGFR - Aleksic, Tamara; Browning, Lisa; Woodward, Martha; Phillips, Rachel; Page, Suzanne; Henderson, Shirley; Athanasou, Nicholas; Ansorge, Olaf; Whitwell, Duncan; Pratap, Sarah; Hassan, A. Bassim; Middleton, Mark R.; et al. (Frontiers in Oncology, 2016)
Chordomas are rare primary malignant bone tumors arising from embryonal notochord remnants of the axial skeleton. Chordomas commonly recur following surgery and radiotherapy, and there is no effective systemic therapy. Previous studies implicated receptor tyrosine kinases including epidermal growth factor receptor (EGFR) and type 1 insulin-like growth factor receptor (IGF-1R) in chordoma biology. We report an adult female patient who presented in 2003 with spinal chordoma, treated with surgery and radiotherapy. She underwent further surgery for recurrent chordoma in 2008, with subsequent progression in pelvic deposits. In June 2009 she was recruited onto the Phase I OSI-906-103 trial of EGFR inhibitor erlotinib with linsitinib, a novel inhibitor of IGF-1R/insulin receptor (INSR). Treatment with 100mg QD erlotinib and 50mg QD linsitinib was well-tolerated, and after 18 months a partial response was achieved by RECIST criteria. From 43 months a protocol modification allowed intra-patient linsitinib dose-escalation to 50mg BID. The patient remained stable on trial treatment for a total of five years, discontinuing treatment in August 2014. She subsequently experienced further disease progression for which she underwent pelvic surgery in April 2015. Analysis of DNA extracted from 2008 (pre-trial) tissue showed that the tumor harbored wild-type EGFR, and a PIK3CA mutation was detected in plasma but not tumor DNA. The 2015 (post-trial) tumor harbored a mutation of uncertain significance in ATM, with no detectable mutations in other components of a 50 gene panel including EGFR, PIK3CA and TP53. By immunohistochemistry the tumor was positive for brachyury, the molecular hallmark of chordoma, and showed weak-moderate membrane and cytoplasmic EGFR. IGF-1R was detected in the plasma membrane and cytoplasm and was expressed more strongly in recurrent tumor than the primary. We also noted heterogeneous nuclear IGF-1R, which has been linked with sensitivity to IGF-1R inhibition. Similar variation in IGF-1R expression and subcellular localization was noted in 15 further cases of chordoma. In summary, this exceptionally durable response suggests that there may be merit in evaluating combined IGF-1R/INSR and EGFR inhibition in patients with chordomas that recur following failure of local treatment.